THE SEMANTIC DEVELOPMENT OF ARABIC WORDS USED IN THE “BABURNAMA” (Eureka Journal of Language, Culture & Social Change, 2026)
This article investigates the semantic development of Arabic loanwords in classical Uzbek on the basis of lexical material attested in the Baburnama. The study proceeds from the premise that borrowed lexemes undergo various degrees of semantic transformation in the recipient language, ranging from full preservation of meaning to semantic expansion, narrowing, or complete shift. Drawing on explanatory dictionaries and contextual analysis, the research identifies patterns of semantic stability and change among Arabic-derived vocabulary in Uzbek. Special attention is given to semantically equivalent loanwords that retain their original meanings across Arabic and Uzbek. The findings demonstrate that many Arabic borrowings have become fully integrated into the Uzbek lexical system and now function as internal resources of the language. The study contributes to ongoing research on lexical-semantic change and the historical dynamics of borrowing in Uzbek.
Keywords: Arabic loanwords; semantic development; semantic expansion; semantic narrowing; semantic shift; Uzbek lexicon; Baburnama; lexical borrowing; semantic equivalence.